A Rapid Graphene Sensor Platform for the Detection of Viral Proteins in Low Volume Samples. Issue 6 (22nd March 2022) - Walters, Ffion; Burwell, Gregory; Mitchell, Jacob John; Ali, Muhammad Munem; Daghigh Ahmadi, Ehsaneh; Mostert, A. Bernardus; Jenkins, Cerys Anne; Rozhko, Sergiy; Kazakova, Olga; Guy, Owen J.
Abstract : Infectious disease outbreaks remain an ever‐prevalent global issue. The associated demand for rapid diagnostics and onsite testing will play an increasing and critical role in disease surveillance, prevention of the spread of infection, as well as timely commencement of treatment. Reported here is a graphene–gold nanoparticle hybrid sensor platform technology that is demonstrated for the real‐time detection of viral proteins utilizing low volume samples (5 μL). Hepatitis C virus (HCV) is still an endemic problem worldwide and is used as an exemplar system here to demonstrate the capability of the platform viral detection sensor technology. Hepatitis C virus core antigen (HCVcAg) is a promising marker for point‐of‐care (POC) diagnostic testing for active HCV infection, with the potential to provide a one‐stop diagnosis and trigger for the commencement of treatment. Real‐time electrical resistance measurements are performed using various concentrations of HCVcAg with linear concentration dependence of resistance on HCVcAg concentration over the range of 100–750 pg mL −1 . Abstract : A graphene–gold nanoparticle (AuNP) hybrid sensor platform is presented as a point‐of‐care (POC) device for the diagnosis of chronic hepatitis C virus (HCV) infection. Real‐time measurements and analysis of the antigen–antibody binding confirm preferential attachment to target sites detectable above the background signal from its media. This suggests a route toward low‐volume detection of viruses in resource‐limited settings.